2022
DOI: 10.3390/agronomy12061270
|View full text |Cite
|
Sign up to set email alerts
|

Soil Waterlogging Conditions Affect Growth, Water Status, and Chlorophyll “a” Fluorescence in Coffee Plants (Coffea arabica L.)

Abstract: Soil waterlogging is an environmental limitation that is promoted by changes in rainfall patterns and negatively affects plant physiology, growth, and development, coffee production, and exports in Colombia. The objective of this research was to evaluate responses in growth, water status, and chlorophyll fluorescence parameters for plants under different waterlogging conditions. The evaluations were carried out on six-month-old “Cenicafé 1” variety seedlings that were suitable for establishment in the field. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Better responses in terms of growth and physiology (stomatal conductance, maximum photochemical efficiency of PSII [Fv/Fm], leaf water potential, relative water content, chlorophyll content, and net photosynthesis) are shown by the cape gooseberry (Physalis peruviana), which was flooded for 6 days with applications of 100 mM GB or H 2 O 2 [110]. Generally speaking, measuring the impact of waterlogging stress can be performed quickly and easily using chlorophyll fluorescence [111][112][113].…”
Section: Solutions Reducing the Waterlogging Stressmentioning
confidence: 99%
“…Better responses in terms of growth and physiology (stomatal conductance, maximum photochemical efficiency of PSII [Fv/Fm], leaf water potential, relative water content, chlorophyll content, and net photosynthesis) are shown by the cape gooseberry (Physalis peruviana), which was flooded for 6 days with applications of 100 mM GB or H 2 O 2 [110]. Generally speaking, measuring the impact of waterlogging stress can be performed quickly and easily using chlorophyll fluorescence [111][112][113].…”
Section: Solutions Reducing the Waterlogging Stressmentioning
confidence: 99%
“…Despite significant strides in understanding the growth and adaptation of the coffee plant, environmental challenges continue to hinder coffee production. Under this scope, León-Burgos et al [15] indicated the harmful effects of soil waterlogging on the growth and physiological performance of C. arabica Cenicafé 1 variety plants. Their findings revealed that 16 days of waterlogging resulted in a considerable reduction in the total dry mass of the plant.…”
Section: Published Articlesmentioning
confidence: 99%
“…1 Under flooded conditions; 2 in some mango varieties; 3 in some species. and easy technique to measure the effect of waterlogging stress (Flórez-Velasco et al, 2015;Sánchez-Reinoso et al, 2019;León-Burgos et al, 2022).…”
Section: Some Measures To Relieve Stress From Waterloggingmentioning
confidence: 99%